Sitting height, sitting height/height ratio, arm span and arm span-height difference of healthy adolescents in Surakarta, Indonesia - Annang Giri Moelyo; Lucky Yogasatria; Yusak Aditya Setyawan; Evi Rokhayati (Paediatrica Indonesiana, 2018)
Background Sitting height, sitting height/height ratio (SHR), arm span, and arm span-height difference (AHD) are indices to diagnose conditions of disproportion. Reference data on sitting height, SHR, arm span, and AHD for Indonesian children are limited. Objective To compile reference data on sitting height, SHR, arm span, and AHD in Indonesian adolescents, and to compare these indices for boys and girls at various ages. Methods A population-based survey was conducted from August 2016 to November 2017 in three high schools in Surakarta, Central Java, Indonesia. A convenience sampling method was employed to recruit healthy adolescents without history of chronic disease, history of physical trauma, and/or physical disabilities. All subjects underwent anthropometric measurements (height, weight, sitting height, and arm span), and their ethnic origins were noted. The lambda-mu-sigma (LMS) method was used for reference construction. Results Of 639 subjects, 42% were male. Body mass index (BMI) values were similar between males and females. Mean height, weight, sitting height, and arm span of males were greater than those of females. The mean male and female SHRs were 51.1 (SD 1.6) % and 51.0 (SD 1.6) %, respectively (P=0.36), while the mean AHDs were 4.2 (SD 4.5) cm and 3.4 (SD 4.1) cm, respectively (P=0.02). The formula to estimate height based on arm span in males was [height = (0.78 x arm span) + 32.14] in cm. The formula in females was [height = (0.66 x arm span) + 50.59] in cm. Conclusion There was no significant difference in SHR between male and female adolescents. However, males haVE significantly larger mean AHD than females. We provide references on sitting height, SHR, arm span, and AHD in male and female adolescents.